Improving the Professional Competence of Indonesian Language Teachers for Foreign Speakers (BIPA) Through the Development of Interactive Digital-Based RANDI Model Training - Rita Retnowati; Come Ramliyani; Prihastuti Harsani (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This study aims to develop an interactive digital-based RANDI training management model to improve the professional competence of Indonesian teachers for Foreign Speakers (BIPA). The RANDI model integrates five main elements: Reframing, Affinity, Neocognitive, Digital Interactive, and Integration. This research uses the Research and Development (R&D) method of Borg and Gall,  with ten systematic stages, starting from information collection to dissemination of final results. Data was obtained through interviews, observations, questionnaires, and professional competency tests. The limited trial was conducted in 15 participants and the broad trial was conducted in 40 participants. Data analysis is carried out in three main stapes: need analysis,a expert validation and product testing. The results showed an increase in the average competency test score from 63 in a limited trial to 71 in a wide trial. The trainees showed an increased understanding of the Indonesian National Work Competency Standards (SKKNI) for BIPA Teachers and were able to implement technology-based teaching materials more effectively. This training model also improves teachers' skills in utilizing interactive digital platforms, such as Google Suite, Kahoot, and Articulate Storyline 3. The RANDI model has proven to be effective and relevant in improving the professional competence of BIPA teachers in the digital era. Thus, this model is expected to be a reference in the development of similar training programs in the future.